Effects of Process Variables on Properties of CoFe2O4 Nanoparticles Prepared by Solvothermal Process - Hong Diu Thi Duong; Dung The Nguyen; Kyo-Seon Kim (Nanomaterials, 2021)
Controlling the morphology and magnetic properties of CoFe2O4 nanoparticles is crucial for the synthesis of compatible materials for different applications. CoFe2O4 nanoparticles were synthesized by a solvothermal method using cobalt nitrate, iron nitrate as precursors, and oleic acid as a surfactant. The formation of CoFe2O4 nanoparticles was systematically observed by adjusting synthesis process conditions including reaction temperature, reaction time, and oleic acid concentration. Nearly spherical, monodispersed CoFe2O4 nanoparticles were formed by changing the reaction time and reaction temperature. The oleic acid-coated CoFe2O4 nanoparticles inhibited the growth of particle size after 1 h and, therefore, the particle size of CoFe2O4 nanoparticles did not change significantly as the reaction time increased. Both without and with low oleic acid concentration, the large-sized cubic CoFe2O4 nanoparticles showing ferromagnetic behavior were synthesized, while the small-sized CoFe2O4 nanoparticles with superparamagnetic properties were obtained for the oleic acid concentration higher than 0.1 M. This study will become a basis for further research in the future to prepare the high-functional CoFe2O4 magnetic nanoparticles by a solvothermal process, which can be applied to bio-separation, biosensors, drug delivery, magnetic hyperthermia, etc.